The space of time - Hitchcock, Peter (Primerjalna književnost, 2013)
This article examines the importance of temporality to any "spatial turn," especially regarding the coordinates of social and cultural crisis, here gathered under the rubric of "the space of time." Although chronotopes are not usually associated with crisis at this scale, they nevertheless address specific levels of impasse in time/space relations. In literary critique, this means not only interrogating the internal effects of spatiality in narrative, for instance, but also considering the extent to which these effects may themselves be overdetermined by deeper social and spatial prerogatives. This not only helps situate the chronotope as a concept in its time but also dialectically explains its prescience for our time.
Keywords: literarna veda; literary science; naratologija; narratology; prostor in čas; kronotop; prostorski obrat; literarna teorija; literary theory; literarne študije